Feasibility study on mobile and communication technologies for language learning - Osman, Mashanum; Chung, Paul W.H. (2010)
This paper describes a study that has been carried out to determine the feasibility for combining mobile and communication technologies for language learning for Malaysian students in higher education. Mobile phone can deliver learning in nugget size at anytime and anywhere to engage learners by providing content, reminders and quizzes. All of these can improve learning experience. Communication tools such as blog and wikis provide a way of sharing ones writing with others, such as ones classmates or team members. Comments and feedback in blogs and wikis can motivate and encourage students to be active participants and further improving their skills. The limitations and implications of the findings of the feasibility to provide directions for a larger study that is to follow.